EFEKTIVITAS PROGRAM PENGINJILAN DI KALANGAN MAHASISWA REGULER - eunike masode; fianus tandiongan; eni rombe (STT Kristus Alfa Omega, 2022)
In this study, it is suspected that the effectiveness of the evangelism program among regular students still less than the maximum marked by the lack of enthusiasm of students in carrying out mandatory evangelism. So the purpose of this research is to find out the effectiveness of the evangelism program among regular students STT Kristus Alfa Omega Semarang Academic Year 2021/2022. The method used is a qualitative research method. Based on the results of interviews and analysis conducted by researchers, then it is known that the implementation of the evangelism program at the STT KAO Semarang is less effective, this can be seen from the implementation of mandatory evangelism has not fully become a lifestyle because of a lack of obedience to God's Word. Evangelism is a must that must be carried out by every believer as a form of love and obedience to God's Word. Therefore, every regular student at STT KAO Semarang needs to experience a renewal of the concept of thinking according to God's Word by involving lecturers to provide teaching what the Bible says about evangelism.